Experimental investigation of the google congestion control for real-time flows - Luca De Cicco; Gaetano Carlucci; Saverio Mascolo (Proceedings of the 2013 ACM SIGCOMM Workshop on Future Human-Centric Multimedia Networking, 2013)
Enabling real-time communication over the Internet is of ever increasing importance due to the use of Internet for audio/video communication. The RTCWeb IETF working group has been established with the goal of standardizing a set of protocols for inter-operable real-time communication among Web browsers. In this paper we experimentally evaluate the Google Congestion Control (GCC) which has been recently proposed in the RTCWeb IETF WG. By setting up a controlled testbed, we have evaluated to what extent GCC flows are able to track the available bandwidth, while minimizing queuing delays, and fairly share the bottleneck with other GCC or TCP flows. We have found that the algorithm works as expected when a GCC flow accesses the bottleneck in isolation, whereas it is not able to provide a fair bandwidth utilization when a GCC flow shares the bottleneck with either a GCC or a TCP flow.
Keywords: Congestion control; real-time flows; rmcat; rtcweb